Erratum: A TPD-based determination of the graphite interlayer cohesion energy (Journal of Chemical Physics (2018) 149 (194701) DOI: 10.1063/1.5052728) - Weippert, Juergen; Hauns, Jakob; Bachmann, Julian; Boettcher, Artur; Yao, Xuelin; Yang, Bo; Narita, Akimitsu; Muellen, Klaus; Kappes, Manfred M. (Journal of Chemical Physics, 2019)
In Fig. 1 of the original article, void space in the figure data was filled with brown beams by the document compiler. These have now been removed (Fig. 1). Due to a communication error, Fig. 5 of the supplementary material also ended up being Fig. 5 of the original article.1 The correct, originally submitted and reviewed Fig. 5 is given. The changes made to the figure do not affect the correctness of the text in the original article; all numbers given there were accurate. In addition, in Subsections III C and III D, the panels 5(a) and 5(b) were referenced as panels 4(a) and 4(b) in three occurrences due to a miscopied hyperlink. (Figure Presented).
CRIS-Team Scopus Importer:2022-04-14